Immediate Role of Two Yoga Based Mantra Recitation on Selective Attention in Undergraduate Students - NAROTTAM KUMAR (Dr. Chinmay Pandya, 2019)
Aim of the present study was to evaluate the effect of Gayatri mantra recitation and Om recitation on selective attention as measured by color stroop. The study was performed on undergraduate students (Male=30) with age range of 18 to 30 years. All students were trained for reciting Gayatri mantra for 3 days. The baseline data were used. The participants participated in Gayatri mantra and Om recitation about 15 min for two consecutive days. The sequence of the session was assigned randomly to the participants. The attention was assessed using color stroop test before and immediately after each session. Within-group comparison showed that due to GM recitation and Om recitation, Stroop scores improved or significant improvement of Stroop scores in both groups (P < 0.001;Wilcoxon signed rank test). The percentage improvement of Stroop score was 16.16 % after GM recitation whereas 9.26 % after Om recitation. This pilot study shows that both Gayatri mantra and simply sitting led to improvement in attention, as measured by Stroop Task. But the influence of Gayatri mantra was significantly higher than Om recitation.